TYPES OF TESTING AND ASSESSMENT IN TEACHING (International Conference on Economics, Finance, Banking and Management, 2025)
Assessment and testing are integral components of the teaching and learning process, serving as essential tools for measuring student progress, guiding instructional decisions, and ensuring educational accountability. This article explores the various types of testing and assessment employed in educational settings, including formative and summative assessments, diagnostic tests, standardized testing, and performance-based evaluations. Each type is examined in terms of its purpose, methodology, advantages, and limitations. The article also discusses the role of assessment in promoting student learning and how educators can use diverse assessment strategies to cater to different learning styles and objectives. By understanding and effectively implementing varied forms of assessment, teachers can foster a more inclusive and effective educational environment.